Peningkatan Kemampuan Berbicara Bahasa Prancis Melalui Model Pembelajaran Kolaboratif - Dian Rusdiana (Indonesian Journal of Applied Linguistics Review, 2017)
The objective of this action research is to find out how to increase the students’ speaking proficiency in French by using collaborative learning method. This research was conducted at Jakarta Tourism Academy. The participants of this research were students of the 2013/2014 academic years joining French Lecturer. The research method used was action research which was conducted in 2 cycles. The procedures of this action research were planning, acting, observing, reflecting, replanning.The result of this research indicates that after being given the action at cycles 1 and 2, the students’ speaking competence in using French increase step by step. Based on the research, it can be concluded that Colaborative learning method in teaching French can increase the students’ French speaking competence.